Adhering to scientific and ethical criteria for scholarship of teaching and learning - Pool, Jessica; Reitsma, Gerda (Critical Studies in Teaching and Learning, 2023)
Despite expanding engagement in Scholarship of Teaching  and  Learning  (SoTL),  clear guidelines  for  ethical  criteria  for  SoTL,  and  the  implementation  thereof  remain  limited.    In this paper we critically  reflect  on  how  the  ethics  criteria  and  processes  impact  on  lecturer engagement  in  SoTL,  and  we  provide  suggestions  for  lecturers, academic developers,  and members  of  scientific  and  ethics  committees  on  how  to  support  research  in  teaching  and learning,  without  losing  the  scholarliness  of  such  research  or  hindering  innovation  in teaching.   This   paper   provides   a   critical   reflection   on   SoTL   and   ethics.   Practical recommendations such as: the adaptation of ethical requirements, consultation between SoTL researchers and ethics committees and acknowledging that SoTL is not  purely  discipline-specific  research,  are  provided.  Taking these  recommendations  into  account  may  support  a better alignment between the ethical application process and the scientific approach of SoTL research.